2019
DOI: 10.1103/physrevb.99.245119
|View full text |Cite
|
Sign up to set email alerts
|

Nernst thermopower of time-reversal breaking type-II Weyl semimetals

Abstract: Weyl semimetals host linear energy dispersions around Weyl nodes, as well as monopoles of Berry curvature in momentum space around these points. These features give rise to unique transport signatures in a Weyl semimetal, such as transverse transport without an applied magnetic field, known as anomalous transport. The type-II Weyl semimetal, recently experimentally demonstrated in several materials, is classified by a tilting of the Weyl nodes. This paper provides a theoretical study on thermoelectric transpor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
(65 reference statements)
0
2
0
Order By: Relevance
“…Similar to the anomalous Hall effect, even without external magnetic field, the Nernst effect can still emerge, called anomalous Nernst effect (ANE). ANE has been extensively studied in ferromagnetic metals, however, given the direct link between ANE and the Berry curvature, it has gained significant recent theoretical (123)(124)(125)(126)(127)(128)(129)(130)(131) and experimental (50)(51)(52)(132)(133)(134)(135)(136)(137)(138) attention in the field of topological Weyl semimetals (Figure 5b).…”
Section: Nernst Hallmark Of Berry Curvaturementioning
confidence: 99%
“…Similar to the anomalous Hall effect, even without external magnetic field, the Nernst effect can still emerge, called anomalous Nernst effect (ANE). ANE has been extensively studied in ferromagnetic metals, however, given the direct link between ANE and the Berry curvature, it has gained significant recent theoretical (123)(124)(125)(126)(127)(128)(129)(130)(131) and experimental (50)(51)(52)(132)(133)(134)(135)(136)(137)(138) attention in the field of topological Weyl semimetals (Figure 5b).…”
Section: Nernst Hallmark Of Berry Curvaturementioning
confidence: 99%
“…(For instance, for the three-dimensional case, the studies on the minimal lattice model [40] were reported in Refs. [41,42].) In the continuous model, however, there is a subtlety of the momentum cut-off dependence, which hampers the study on the transport coefficients of all the three types in an equal-footing manner.…”
Section: Introductionmentioning
confidence: 99%